Republic of Mozambique : Report on Observance of Standards and Codes; Fiscal Transparency Module. (IMF Staff Country Reports; Country Report ;, 2008)
This report provides a reassessment of fiscal transparency practices in Mozambique. The reassessment is conducted against the results of Report on the Observance of Standards and Codes (ROSC) on fiscal transparency, which identified serious transparency shortcomings and updates of the ROSC, Public Expenditure and Financial Accountability (PEFA) Assessment, and FAD technical assistance missions, which have indicated some progress on improving fiscal transparency. However, the intense pace of fiscal reforms implemented over the last few years calls for conducting a complete reassessment of Mozambique's compliance with the requirements of the IMF Code of Good Practices of Fiscal Transparency.